Performance limits of seismically isolated buildings under near-field earthquakes. (1st June 2016) - Alhan, Cenk; Öncü-Davas, Seda
Highlights: Methodology for assessing performance limits of seismic isolation system design. Seismic actions on contents are explicitly considered in isolation system design. Optimum isolation system parameters required to satisfy a target performance limit. May protect structural integrity under large magnitude near-field earthquakes. Challenging to protect equipment under large magnitude near field earthquakes. Abstract: The mission of seismic isolation is two folds: (i) protecting the integrity and (ii) protecting the contents of a structure by reducing floor accelerations to target limits and concurrently keeping base displacements below practical and economical limits. To this end, while seismic isolation has proven to be successful under far-field earthquakes, its success in case of near-field earthquakes is being questioned for over a decade now; the main reason being the threat of excessive base displacements due to the presence of long period large velocity pulses. Lowering isolation period and increasing isolation damping aiming to reduce base displacements unfortunately may result in a reduced seismic performance in terms of floor accelerations particularly under far-field earthquakes. And the success level of such a precaution under near-field earthquakes depends both on the fault-distance and the pulse period to the isolation period ratio. Thus, the aim of this study is to evaluate the performance limits of buildings equipped with seismic isolation systems of different characteristics when subjected to near-field ground motions at different fault distances with different velocity pulse periods. Accordingly, a methodology for assessing the performance limit of a seismic isolation system design that explicitly considers the seismic actions on the contents of the superstructure in the near-field region is introduced. Benchmark buildings with base isolation systems of different isolation periods and characteristic force ratios are subjected to synthetically developed near-field earthquake records at different fault-distances with different velocity pulse periods and their seismic performances are reported.